2006
DOI: 10.1029/2006ja011660
|View full text |Cite
|
Sign up to set email alerts
|

Striated auroral kilometric radiation emission: A remote tracer of ion solitary structures

Abstract: [1] We describe the statistical properties of narrowband drifting auroral kilometric radiation (''striated'' AKR) based on observations from the Cluster wideband receiver during [2002][2003][2004][2005]. We show that the observed characteristics, including frequency drift rate and direction, narrow bandwidth, observed intensity, and beaming angular sizes are all consistent with triggering by upward traveling ion solitary structures (''ion holes''). We calculate the expected perturbation of a horseshoe electron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 51 publications
2
68
0
Order By: Relevance
“…While it may be reasonable to regard commonly observed AKR generally as ensembles of emissions from distributions of 'elemental radiators' (Pottelette et al 2001), it is not clear if all AKR is comprised of only SAKR bursts. The observations reported by Mutel et al (2006) showed that SAKR appeared as negatively drifting features (df/dt < 0) superposed on regular broadband AKR background. These observations suggest that the SAKR-producing structures are ion holes moving upward through coeval AKR sources, although this scenario does not account for the upward (df/dt > 0) or nearly constant (df/dt ∼ 0) spectral striations seen in earlier observations (Gurnett et al 1979;Gurnett and Anderson 1981;Menietti et al 1996Menietti et al , 2000.…”
Section: Betatron and Stochastic Accelerationmentioning
confidence: 99%
See 4 more Smart Citations
“…While it may be reasonable to regard commonly observed AKR generally as ensembles of emissions from distributions of 'elemental radiators' (Pottelette et al 2001), it is not clear if all AKR is comprised of only SAKR bursts. The observations reported by Mutel et al (2006) showed that SAKR appeared as negatively drifting features (df/dt < 0) superposed on regular broadband AKR background. These observations suggest that the SAKR-producing structures are ion holes moving upward through coeval AKR sources, although this scenario does not account for the upward (df/dt > 0) or nearly constant (df/dt ∼ 0) spectral striations seen in earlier observations (Gurnett et al 1979;Gurnett and Anderson 1981;Menietti et al 1996Menietti et al , 2000.…”
Section: Betatron and Stochastic Accelerationmentioning
confidence: 99%
“…However, the Cluster ESW propagation studies prove that ESWs are not intrinsically unstable, which helps to bound the problem when considering how they are generated. This was an important issue in the study by Mutel et al (2006), which concluded that ion solitary waves passing through the AKR generation region affected the CMI, leading to the striations discussed above.…”
Section: Electrostatic Solitary Wavesmentioning
confidence: 99%
See 3 more Smart Citations